Development and characterization of agonistic antibodies targeting the Ig-like 1 domain of MuSK - Jamie L. Lim; Roy Augustinus; Jaap J. Plomp; Kasra Roya-Kouchaki; Dana L. E. Vergoossen; Yvonne Fillié-Grijpma; Josephine Struijk; Rachel Thomas; Daniela Salvatori; Christophe Steyaert; Christophe Blanchetot; Roeland Vanhauwaert; et al. (Scientific Reports, 2023)
Abstract Muscle-specific kinase (MuSK) is crucial for acetylcholine receptor (AChR) clustering and thereby neuromuscular junction (NMJ) function. NMJ dysfunction is a hallmark of several neuromuscular diseases, including MuSK myasthenia gravis. Aiming to restore NMJ function, we generated several agonist monoclonal antibodies targeting the MuSK Ig-like 1 domain. These activated MuSK and induced AChR clustering in cultured myotubes. The most potent agonists partially rescued myasthenic effects of MuSK myasthenia gravis patient IgG autoantibodies in vitro. In an IgG4 passive transfer MuSK myasthenia model in NOD/SCID mice, MuSK agonists caused accelerated weight loss and no rescue of myasthenic features. The MuSK Ig-like 1 domain agonists unexpectedly caused sudden death in a large proportion of male C57BL/6 mice (but not female or NOD/SCID mice), likely caused by a urologic syndrome. In conclusion, these agonists rescued pathogenic effects in myasthenia models in vitro, but not in vivo. The sudden death in male mice of one of the tested mouse strains revealed an unexpected and unexplained role for MuSK outside skeletal muscle, thereby hampering further (pre-) clinical development of these clones. Future research should investigate whether other Ig-like 1 domain MuSK antibodies, binding different epitopes, do hold a safe therapeutic promise.